Harald Motzki's Thought in Hadith Studies: An Analysis of the Authenticity of the Ṣaḥīfah of ʿAbd al-Razzāq - Rahmad Ridwan (Jurnal Penelitian Medan Agama, 2026)
The objective of this study is to analyze Harald Motzki’s approach to hadith studies, specifically through the application of the isnād-cum-matn analysis method to Shaifah ‘Abd al-Razzāq as one of the early sources of hadith in Islam. This study is motivated by the dominance of the Orientalist skepticism paradigm in hadith studies pioneered by Ignaz Goldziher and Joseph Schacht, which tends to cast doubt on the authenticity of hadith. This research employs a qualitative approach using library research methods through an examination of Harald Motzki’s works and literature related to contemporary hadith studies. The results of the study indicate that Motzki offers a more empirical and moderate approach compared to earlier Orientalists by simultaneously integrating the analysis of isnād and matn. Through his analysis of Shaifah ‘Abd al-Razzāq, Motzki successfully demonstrates that some hadith narrations have historical roots traceable to the early generations of Islam. The novelty of this study lies in its examination of the concrete application of the isnād-cum-matn analysis method in reconstructing the authenticity of hadith, rather than merely focusing on the biographical aspects or general ideas of Harald Motzki. This study contributes to enriching the methodology of contemporary hadith studies while opening a space for dialogue between the classical Islamic tradition of hadith criticism and modern Western historical approaches.